JOB DEMANDS DAN BURNOUT PADA GURU SEKOLAH LUAR BIASA (SLB) NEGERI - DWI KENCANA WULAN; ADELIA CITRA APRILIANI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
This study aims to determine the effect of job demands on burnout in public special school teachers. There are 126 subjects who were choosen by using the purposive sampling technique. This study uses quantitative method. The data collection technique in this study uses instruments which has been adapted based on from Maslach Burnout Inventory (MBI) and Job Demands-Resources Questionnaire. The hypothesis was tested using the linier regression analysis one predictor. The result shows the score of F count 27,704 > F table 3,94 with significant value 0,000 (p > 0,05). It means, there is significant effect of job demands on burnout in public special school teachers. The effect of job demands on burnout is 18,3 %.